The Effect of Walking Exercise on Blood Pressure Changes in the Elderly in Social Institutions - Muh. Yani; Wa Ode Nurlina; Glorya Riana Latupeirissa; Endri Mustofa; Faysal Kastella (Indonesian Journal of Global Health Research, 2022)
One of the causes of hypertension is reduced physical activity. Physical activity that can be done to maintain blood pressure stability is walking. This study aims to determine the effect of walking exercise blood pressure in elderly with hypertension in nursing homes. This study uses a design that is pre experimental one group pre test - post test design. The population in this study were the elderly at the Trisna Werda Social Institution, Gowa Regency, namely 100 people. Sampling was selected by purposive sampling. Retrieval of data using the instrument observation sheet. Bivariate analysis using the Wilcoxon test. From the results of the research on the effect of walking exercise on changes in blood pressure in the elderly at the Trisna Werda Social Institution with a total sample of 30 people, it can be concluded that respondents with the pre-test blood pressure category who experienced special blood pressure were as much as (50.0%). Respondents in the post-test blood pressure category who experienced special blood pressure decreased to (23.3%). Seeing the results, it can be concluded that there is an effect of running on changes in blood pressure in the elderly at the Trisna Werda Social Institution.